2022
DOI: 10.1038/s41467-022-34511-2
|View full text |Cite|
|
Sign up to set email alerts
|

Structural dynamics of AAA + ATPase Drg1 and mechanism of benzo-diazaborine inhibition

Abstract: The type II AAA + ATPase Drg1 is a ribosome assembly factor, functioning to release Rlp24 from the pre-60S particle just exported from nucleus, and its activity in can be inhibited by a drug molecule diazaborine. However, molecular mechanisms of Drg1-mediated Rlp24 removal and diazaborine-mediated inhibition are not fully understood. Here, we report Drg1 structures in different nucleotide-binding and benzo-diazaborine treated states. Drg1 hexamers transits between two extreme conformations (planar or helical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…From the improved map of the NBD ring, the substrate density in the central channel could be unambiguously identified ( S4D Fig ). In general, the helical arrangement of subunits within a hexamer is highly similar to other substrate-bound AAA+ ATPases [ 7 , 25 , 28 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the improved map of the NBD ring, the substrate density in the central channel could be unambiguously identified ( S4D Fig ). In general, the helical arrangement of subunits within a hexamer is highly similar to other substrate-bound AAA+ ATPases [ 7 , 25 , 28 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…For most of the AAA + proteins, this mutation would greatly slow down ATP hydrolysis but not ATP binding. Structural studies of a few AAA+ unfoldases/disaggregases showed that this mutation often resulted in a co-purification of endogenous peptide in the central channel [25][26][27][28]. Therefore, we prepared CLPB E425Q mutant from E. coli cells (S2C and S2D S5B).…”
Section: Plos Biologymentioning
confidence: 99%
“…The structures of p97 and its yeast homolog bound to substrates show a large change in conformation in the D1 and D2 domains, with splitting of the rings into a washer-like conformation and a staggered arrangement of the domains along the unfolded substrate [ 17 , 18 , 51 , 52 , 53 , 54 ]. Co-factors recruit the substrate to p97, yet how they promote substrate engagement remains unknown at the mechanistic level, as they are mostly not resolved in the substrate-engaged conformations due to their intrinsic flexibility.…”
Section: Introductionmentioning
confidence: 99%